PENERAPAN MEDIA KARTU BILANGAN PADA PEMBELAJARAN MATEMATIKA SISWA KELAS II SD NEGERI 4 MEGANG SAKTI - Tika Avrianti; Elya Rosalina; Aswarliansyah Aswarliansyah (JOURNAL of MATHEMATICS SCIENCE and EDUCATION, 2021)
The research objective was to determine the completeness of learning outcomes in the application of number card media in mathematics learning for grade II students of SD Negeri 4 Megang Sakti. This research method uses an experimental research method with a quasi-experimental design with the categories of pre-test and post-test group. The subjects of this study were 11 grade students of SD Negeri 4 Megang Sakti. The data collection technique uses a test technique in the form of 6 essay questions. The data were analyzed using the "z" test formula. Based on the data analysis, it is known that the results of the pre-test with an average value of 41.591 and the final test (post-test) score of 83.364. Based on the results of hypothesis testing, then zcount is compared with zcount with a significant level of α = 0.05, obtained z_hitung 11.036 and z_table 1.645, then z_hitung 11.036> z_table 1.645 with this, H_a is accepted and H_O is rejected. So it can be concluded that the application of the number card media for the learning outcomes of grade II SD Negeri 4 Megang Sakti is significantly complete.